Deletion of Puma protects hematopoietic stem cells and confers long-term survival in response to high-dose γ-irradiation - Yu, Hui (American Society of Hematology, 2010)
Molecular paradigms underlying the death of hematopoietic stem cells (HSCs) induced by ionizing radiation are poorly defined. We have examined the role of Puma (p53 up-regulated mediator of apoptosis) in apoptosis of HSCs after radiation injury. In the absence of Puma, HSCs were highly resistant to γ-radiation in a cell autonomous manner. As a result, Puma-null mice or the wild-type mice reconstituted with Puma-null bone marrow cells were strikingly able to survive for a long term after high-dose γ-radiation that normally would pose 100% lethality on wild-type animals. Interestingly, there was no increase of malignancy in the exposed animals. Such profound beneficial effects of Puma deficiency were likely associated with better maintained quiescence and more efficient DNA repair in the stem cells. This study demonstrates that Puma is a unique mediator in radiation-induced death of HSCs. Puma may be a potential target for developing an effective treatment aimed to protect HSCs from lethal radiation.